NEW TAXA IN INDONESIAN BAMBOOS - Widjaja, Elizabeth Anita (Research Center for Biology, 1997)
From a recent research on Indonesian bamboo germplasm it has become evident that there are at least 43 undescribed species (6 species of Bambusa, 3 species of Dendrocalamus, 4 species of Dinochloa, 13 species of Gigantochloa, 2 species of Nastus, 2 species of Racemobambos, 11 species of Schizostachyum and 2 species in the new monotyic genera Parabambusa and Pinga). Two new genera (Fimbribambusa and Neololeba) are here separated from Bambusa Schreb.